Multiplier Effect of the Education and Economy in Center Point of Indonesia Area - Natsir, Uhud Darmawan; Aswar, Nurul Fadilah; Lestari, Dwi Anugerah (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Infrastructure development was one of the key components in the success of a nation's overall and educational growth, including the tourism sector. This study focuses on analyzing the economic and educational impact of developing the Center Point of Indonesia (CPI) area in Makassar City, South Sulawesi, which has become a prominent tourism destination. A mixed-methods approach with a concurrent triangulation design was employed to measure the direct, indirect, and induced economic and educational impacts of tourism activities within the CPI area. The findings indicated that the development of CPI had a significant economic impact on the surrounding community, including increased business revenues, job creation, and a reduction in poverty levels. Apart from that, the development of CPI as a multifunctional area is impacting education, especially community economic education. The Multiplier Effect analysis, using the Keynesian Income Multiplier method, revealed that every 1 rupiah of tourist expenditure generated a direct economic impact of 19,81 rupiah on the local economy. The Type I Income Multiplier Ratio of 1,062 reflected an increase in the incomes of business owners and workers, while the Type II Income Multiplier Ratio of 1,092 demonstrated its influence on local household consumption. This indicates that the impact of multifunctional infrastructure development has an impact on the economic education of society.